Educational Values in The Novel 'Sepatu Dahlan' by Khrisna Pabichara - Abdulloh Abdulloh; Fransisca S.O. Dedi; Dinda Adelia (IJLHE: International Journal of Language, Humanities, and Education, 2023)
The issues in this research are related to the messages conveying educational values of diversity, resilience, holistic intelligence (identity discovery), responsibility, attitude towards life, and poverty found in literary works (novels). This study aims to identify and analyze the educational values, namely diversity, resilience, holistic intelligence (identity discovery), responsibility, attitude towards life, and poverty, present in the novel "Sepatu Dahlan" by Khrisna Pabichara. The method used in this research is a qualitative descriptive method, which involves analyzing sentence by sentence related to educational values. With this method, the collected data is identified, analyzed, described, and then interpreted according to the predetermined objectives. The choice of descriptive method and qualitative research type is due to the nature of the collected data, which consists of words but emphasizes a deep understanding of the interaction between empirically studied concepts. The research findings indicate that the educational values described in this novel include diversity, resilience, holistic intelligence, responsibility, attitude toward life, and poverty. Hopefully, this novel is useful for all of us and can serve as a source of inspiration for the younger generation in achieving their aspirations, as poverty is not a barrier to rising and pursuing goals, and education plays a significant role in this process.